Development of the First Phase of the Implementation Roadmap of Artificial Intelligence Systems in the HAdEES-C Analog Station (2025)
This report presents the development of the first phase of the Implementation Roadmap for Artificial Intelligence (AI) Systems in HAdEES-C, Colombia's first analog station. AI is one of the technologies currently being researched and applied in space missions through expert systems, intelligent assistants, generative models for problem-solving, psychological support companions, and data analysis tools. These technologies aim to enhance the safety and efficiency of crewed missions. Analog stations like HAdEES-C offer controlled environments to test and validate AI systems tailored to mission needs. Phase 1 consists on creating a cloud-based assistant that provides the crew with immediate access to information about the habitat, but its main component is the characterization of crew needs and the identification of system integration points to understand the key areas where AI can add value. To achieve the project's objective, it was structured to be developed simultaneously with the Valquiria and Meadaivú missions. A baseline for system performance and functionality was also established, which allows systematic and continuous monitoring of its evolution throughout future missions. As it is a scalable platform, it is intended to make it more robust with new functionalities in future phases. The implementation of AI in HAdEES-C during Phase 1 optimized habitat operations, established a framework for continuous improvement, and laid the groundwork for future integrations, reinforcing HAdEES-C as a testbed for innovative space research.